1989
DOI: 10.1111/j.1365-2125.1989.tb05391.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically‐determined interaction between propafenone and low dose quinidine: role of active metabolites in modulating net drug effect.

Abstract: 1 Quinidine is a potent inhibitor of the genetically-determined debrisoquine 4-hydroxylation. Oxidation reactions of several other drugs, including the 5-hydroxylation of the new antiarrhythmic drug propafenone, depend on the isozyme responsible for debrisoquine 4-hydroxylation.2 The effect of quinidine on the debrisoquine phenotype-dependent 5-hydroxylation and the pharmacological activity of propafenone was studied in seven 'extensive' metabolizers and two 'poor' metabolizers of the drug receiving propafenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Despite the changes in plasma concentrations of the 2 substances, no significant change in heart rate, QRS, PR or QTc intervals was noted. No significant interaction was observed in those with the poor metaboliser phenotype (Funck-Brentano et al 1989). …”
Section: Interaction With Quinidinementioning
confidence: 82%
“…Despite the changes in plasma concentrations of the 2 substances, no significant change in heart rate, QRS, PR or QTc intervals was noted. No significant interaction was observed in those with the poor metaboliser phenotype (Funck-Brentano et al 1989). …”
Section: Interaction With Quinidinementioning
confidence: 82%
“…Therefore propafenone is likely to have a pharmacokinetic interaction with CYP2D6 inhibitors. A previous study in white subjects found that low‐dose quinidine, a potent inhibitor of CYP2D6, increased total propafenone plasma concentration in patients with arrhythmia but caused no changes in QRS interval 13 . Another pharmacodynamic study showed that low‐dose quinidine significantly increased the extent of propafenone‐induced β‐blockade 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to their clinical sensitivity and apparent dependency on CYP2D6 in the metabolism (table 3), care should be paid with respect to coadministration of CYP2D6 inhibitors. The same applies for propafenone, where an almost 3-fold increase in exposure was reported during concurrent use of quinidine [61]. Regarding encainide, whose principal activity is mediated through the metabolite produced by CYP2D6, two studies with quinidine had contradictory results (table 8).…”
Section: Relative Exposure Of Cvds With Cyp2d6 Inhibitorsmentioning
confidence: 96%